PENGARUH FAKTOR MAKRO EKONOMI, KEPUTUSAN INVESTASI, DAN KEPUTUSAN PENDANAAN TERHADAP NILAI PERUSAHAAN (STUDI PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI) - Maula Alfina Maulidah; Ida Ayu Sri Brahmayanti (CV. Adiba Aisha Amira, 2026)
This study aims to analyze the effect of macroeconomic factors, investment decisions, and financing decisions on the value of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the period 2019–2023. Company value is proxied by Price to Book Value (PBV), macroeconomic factors by interest rates, inflation, and exchange rates, investment decisions by Price Earning Ratio (PER), and financing decisions by Debt to Equity Ratio (DER). The study uses a quantitative method with purposive sampling of 19 companies with 95 observations. Secondary data were analyzed using multiple linear regression. The results showed that inflation, investment decisions, and financing decisions had a positive and significant effect on company value, while interest rates and exchange rates had no significant effect. Simultaneously, all independent variables had a significant effect on the value of companies in the food and beverage sub-sector